A Linguistic Model of Communication Types in Palliative Medicine: Effects of Multidrug-Resistant Organisms (MDRO) Colonization or Infection and Isolation Measures in End of Life on Family Caregivers’ Knowledge, Attitude and Practices. - Peters, Joachim; Dykes, Nathan; Heckel, Maria; Ostgathe, Christoph; Habermann, Mechthild (Journal of Palliative Medicine, 2019)

A quantitative evaluation of keyword measures for corpus-based discourse analysis - Evert, Stephanie; Dykes, Nathan; Peters, Joachim (2018)

Correction: Possible age-related differences in healthcare professionals’ perspectives on younger and older patients’ autonomy and decision-making in the context of sedation in specialised palliative care: exploratory secondary qualitative content and linguistic conversation analysis of interviews with healthcare professionals (BMC Palliative Care, (2022), 21, 1, (71), 10.1186/s12904-022-00963-y) - Kurkowski, Sandra; Heckel, Maria; Pfaller, Larissa; Peters, Joachim; Bazata, Jeremias; Schildmann, Eva; Ostgathe, Christoph (BMC Palliative Care, 2022)
Following the publication of the original article [1], the author reported that the given name and family name of all authors were erroneously transposed. The author group has been updated above and the original article [1] has been corrected.
CRIS-Team Scopus Importer:2022-09-09

Den Feind beschreiben: Multiresistente Erreger im deutschen Pressediskurs. Eine diskurslinguistische Untersuchung der Jahre 1994–2015. - Peters, Joachim (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2017)

Die Entstehung einer professionalisierten Fachkultur in der Palliativmedizin - sprachwissenschaftliche Perspektiven - Peters, Joachim; Heckel, Maria; Ostgathe, Christoph; Habermann, Mechthild (12. Kongress der Deutschen Gesellschaft für Palliativmedizin, 2018)

Die Palliativmedizinische Fachkultur in Geschichte und Gegenwart – sprachwissenschaftliche Perspektiven - Peters, Joachim; Dykes, Nathan (Linguistik und Medizin, 2022)

Dominic Harion: Mehrsprachige urbane Verwaltungspraxis: Eine Studie zu Sprachverhältnissen und Sprachwahlmechanismen in den Luxemburger ‚Pièces des Comptes‘ des 17. Jahrhunderts - Peters, Joachim (Zeitschrift für deutsche Philologie, 2024)

Ein Fest beschreiben: Zeugnisse der Landshuter Hochzeit in ritual- und konsumgeschichtlicher Perspektive - Peters, Joachim (Verhandlungen des Historischen Vereins für Niederbayern, 2014)

Fachdiskurs, Fachsprache und zentrale Konzepte von Palliativmedizin und Palliativversorgung im 21. Jahrhundert. Eine korpusbasierte linguistische Diskursanalyse an Fachtexten der Jahre 2000–2019. - Peters, Joachim (FAU Unipress, 2021)

From keywords to discourse - towards a keyword operationalisation model in discourse linguistics - Peters, Joachim; Dykes, Nathan (Corpora and Discourse International Conference, 2018)

Gotisch - Peters, Joachim (2018)

Knowledge and Public Perception of Palliative Care in Germany - Heckel, Maria; Peters, Joachim; Schweighart, Susanna; Habermann, Mechthild; Ostgathe, Christoph (Journal of palliative medicine, 2024)
Background: Literature reviews reveal poor knowledge and awareness of palliative care in the public. Health literacy deficits impact access to palliative care. Objectives: The aim of this manuscript is to explore the public perception of palliative care in Germany. Design: Triangulated qualitative research design: a snowball-spread online survey and a random pedestrian survey. Setting/Subjects: Citizens in Germany. Results: The pedestrian survey (n = 100) revealed 34% of the participants being not familiar with palliative care. The online survey (n = 994) 5.7% of participants reported to not know what palliative care was. The public's perception of palliative care is mainly medicine oriented, referring to inpatient care for the immediately dying; however, further significant misperceptions were scarce. Conclusions: The public perception shows an indistinct picture of palliative care, and some misconceptions about the objectives and areas of responsibility of the subject, meanwhile, palliative care is known to a majority of people. Understanding partly incomplete pictures of patients and relatives may help to react appropriately in staff-patient interactions and improve public relations.
CRIS-Team Scopus Importer:2024-04-26
Keywords: attitudes; health knowledge; health literacy; palliative care; practice; public health; terminal care

Kompetenzdarstellung, Patientennähe und Argumentationsstrategien von Internetangeboten deutscher Hospize, Palliativstationen und SAPV-Teams-eine korpusbasierte Meta-Analyse - Peters, Joachim; Dykes, Nathan; Ostgathe, Christoph; Habermann, Mechthild; Heckel, Maria (Zeitschrift für Palliativmedizin, 2020)

Language in Motion - Time-Typical Vocabulary of Palliative Medicine - Peters, Joachim; Heckel, Maria; Habermann, Mechthild; Ostgathe, Christoph (Zeitschrift für Palliativmedizin, 2019)
Background Modern palliative medicine is a young discipline that has developed its independent profile with specific guiding concepts, goals and values. The history of the subject and the development of a palliative vocabulary can be explored by analysing specialised publications.
CRIS-Team WoS Importer:2019-05-28

Lesbar – Sichtbar – Kommuniziert: Bezüge zur logopädischen Tätigkeit in der deutschsprachigen Fachliteratur zu Palliativversorgung - Hensel, Theresa; Peters, Joachim (Forum Logopädie, 2021)

Mehrsprachige urbane Verwaltungspraxis. Eine Studie zu Sprachverhältnissen und Sprachwahlmechanismen in den Luxemburger Pièces des Comptes des 17. Jahrhunderts (Review) - Peters, Joachim (Zeitschrift für deutsche Philologie, 2024)

Metaphors for multidrug-resistant bacteria in German newspaper articles, 1995-2015. A computer-assisted qualitative study. - Peters, Joachim; Dykes, Nathan; Habermann, Mechthild; Ostgathe, Christoph; Heckel, Maria (Metaphor and the Social World, 2019)

Öffentliche Wahrnehmung von Palliativversorgung vor, während und nach der COVID-19-Pandemie – eine empirische Untersuchung von Online-Diskursen - Peters, Joachim; Rabenstein, Ulrich; Heckel, Maria; Breindl, Eva; Ostgathe, Christoph (Zeitschrift für Palliativmedizin, 2024)

Palliativversorgung in Zeiten der COVID-19-Pandemie: Wandelt sich die öffentliche Wahrnehmung? (Abstract) - Peters, Joachim; Rabenstein, Ulrich; Heckel, Maria; Breindl, Eva; Ostgathe, Christoph (Zeitschrift für Palliativmedizin, 2022)

Possible age-related differences in healthcare professionals’ perspectives on younger and older patients’ autonomy and decision-making in the context of sedation in specialised palliative care: exploratory secondary qualitative content and linguistic conversation analysis of interviews with healthcare professionals - Kurkowski, Sandra; Heckel, Maria; Pfaller, Larissa; Peters, Joachim; Jeremias, Bazata; Eva, Schildmann; Ostgathe, Christoph (BMC Palliative Care, 2022)
Background Chronic illnesses and multi-morbidity can threaten competence and independence, particularly in old age. Autonomy becomes increasingly important in the context of sedation, as in this case medication leads to (further) changes of consciousness. The study aimed to identify possible age-related differences in the perspectives of healthcare professionals on patients’ autonomy, in the context of sedation in specialised palliative care. Method Secondary analysis of interviews with healthcare professionals, analysed by qualitative content and linguistic conversation analysis. The interviews analysed span 51 healthcare professionals in specialised palliative care across 17 centres (adult inpatient and specialist palliative home care services) in Germany. Results The study shows that the perspectives of healthcare professionals on patients’ autonomy differs according to the age of the patient in the context of sedation in specialised palliative care. The different perspectives may lead to different ways of treating the patients, for example a greater space of autonomy and decision-making for younger patients. Conclusion In particular, measures that may restrict consciousness (e.g. sedation) and thus influence patients’ ability to fully exercise their autonomy and fully participate in decision-making require special attention by healthcare professionals with respect to possible influences on treatment, such as different perceptions by healthcare professionals based on the patient’s age or age-related stereotype
Keywords: End of life care; Palliative care; Age; Ageing; Autonomy; Qualitative content analysis; Linguistic conversation analysis

Präsentation von Palliativstationen und SAPV-Teams im Internet - eine korpusbasierte Metaanalyse von Webseiten - Peters, Joachim; Dykes, Nathan; Heckel, Maria; Ostgathe, Christoph; Habermann, Mechthild (Zeitschrift für Palliativmedizin, 2022)

Presseethik und Diskursmechanismen im 17. Jahrundert? Überlegungen zu Tobias Peucers 'De relationibus novellis' - Peters, Joachim (Contingentia, 2019)

Reconstructing argumentation patterns in German newspaper articles on multidrug-resistant pathogens: a multi-measure keyword approach - Dykes, Nathan; Peters, Joachim (Journal of Corpora and Discourse Studies, 2020)

Sprache in Bewegung – Schlüsselbegriffe der Palliativmedizin im Wandel der Zeit - Peters, Joachim; Heckel, Maria; Ostgathe, Christoph; Habermann, Mechthild (Zeitschrift für Palliativmedizin, 2019)

Vandalisch - Peters, Joachim (2018)

Vmb Pracht und Hoffarts willen: Luxuskonsum, Repräsentation und die Reglementierung von Geselligkeit in der Nürnberger Policeygesetzgebung des 17. Jahrhunderts - Peters, Joachim (Regionale Konsumgeschichte vom Mittelalter bis zur Moderne, 2015)

Vormittags rien fait quj vaille - Codeswitching im Fürstentagebuch Christians von Anhalt-Bernburg (1599–1656) - Peters, Joachim; Freund, Sabrina (Historisches Codeswitching mit Deutsch, 2021)

What Does “Palliative” Mean? Sentiment, Knowledge, and Public Perception Concerning Palliative Care on the Internet since the COVID-19 Pandemic - Peters, Joachim; Heckel, Maria; Breindl, Eva; Ostgathe, Christoph (Palliative Medicine Reports, 2024)

Zwischen konfessioneller Parteibildung und Friedenshoffnung – ein korpuslinguistischer Zugang zur Kriegsberichterstattung in der Zeit des Dreißigjährigen Krieges - Peters, Joachim (Sprache, Reformation, Konfessionalisierung, 2018)